Potencial antimicrobiano e toxicológico de Alternanthera brasiliana (L.) Kuntze, Amaranthaceae, e o controle de fungos fitopatogênicos - Nicareta, Cleiton (2019)
The plant Alternanthera brasiliana(L.) Kuntze, is popularly known as penicillin due to the antibacterial effects of its extracts. In the literature the studies reporting its composition mainly of phenolic compounds and antimicrobial activity, but not for its ecotoxicological and embryotoxicological activity. The objective of this study was to determine the antimicrobial and toxicological potential of extracts of plant leaves, alcoholic extract (EA), infusion (I) and maceration (M) and its essential oil (OE) and the relation in the control of phytopathogenic fungi such as Botrytis cinerea, Diplodiasp, Fusarium sp and Sclerotinia sclerotiorum. After the extractive processes were carried out, pharmacognostic, phytochemical, chromatographic, antimicrobial studies: determination of the minimum inhibitory concentration (MIC),by the microdilution technique in broth and agar dilution, determining dm (mean diameter of mycelial growth), vm medium mycelial growth) and MIC (microbial growth inhibition percentage), microscopic and toxicological: ecotoxicology tests with Artemia salinaand Embryotoxicology tests with Gallus gallusdomesticus L. embryos Phytochemical and chromatographic studies (thin layer chromatography, CCD High -performance liquid chromatography (HPLC) and gas chromatography coupled to the mass spectrometer (CG -MS), determined the main presence in the plant preparations of phenolic compounds, organic acids, triterpenoids and alkaloids. The extracts presented a CIM considered high, found the lowest values for essential oil. The Poisoned food agar dilution assay was double factorial (Extract × Concentration) with an additional treatment (control of growth / control) in a completely randomized design (DIC) with 4 replicates. In this after statistical analysis, there was a significance of 5%, mainly for the study of Botrytis cinerea, Diplodiasp, Fusariumspand Sclerotinia SclerotiorumFungi, being EA with the best values of PCIM, inhibiting 69%, probably related to the major phenolic compound, ferrúlico acid and also may be responsible for the effects on the microscopic structure of fungi. The ecotoxic effect (invertebrate beings) of the extracts on A. salina, was considered high obtaining as Lethal Concentration at 50% of the sample (LC50): AE = 368.5 μg / mL; I = 322.4 μg / mL: M = 344.4 μg / mL; EO = 94.8 μg / mL. The Embryotoxicology test (vertebrate beings) showed that the preparations of the plant do not present toxic effects on the embryos of Gallus gallus. Therefore, it is concluded that the extracts of the leaves of A. brasilianapresent antimicrobial potential on phytopathogenic fungi and toxic effect on invertebrates and that there is possibility of its use in the control of fungi that reach the most varied agricultural crops.